Basic Principles for the Creation of a National Automated System for Permanent Loss of Working Capacity - Peevsky, T. D.; Gloutnikova, Z. N.; Nicholova, V. I. (Methods of Information in Medicine, 1975)
The System for the Observation and Analysis of Disability is part of the Unified National System for Health Service in Bulgaria.The system was designed after a detailed analysis of the incoming documents and their circulation had been performed and after various models had been designed and tested.Some of the basic tables describing the output of the system are shown. The information from these tables is designed for the various levels of administration which are the carriers of social activities in the country and for the management of the Boards of Experts on Industrial Medicine.
Keywords: EDP in Public Health; Structure Analysis; Disability